Literasi Mahasiswa Mengenai Start up Business (Studi Kasus Di Universitas Nasional Karangturi Semarang) - Wulandari; Tiara Rani Santoso; Lakhmudin; Ratih Kumala Dewi; Novita Sari (Fakultas Ekonomi dan Bisnis, 2021)
internet supported technological progress impacts economic growth. Various business innovations are facilitated by the technology, among them is start up business which has become a trending topic in the society. This research aims to figure out literacy level on start up business. The findings identify 76% university students have Well Literate start up business literacy level. The research applies qualitative approach with observation technique by interviewing the students as respondents.